Ethics, Discovery, and Strategy - Foss, Nicolai J. (Journal of business ethics, 1997)
I address the issue of justifiable profits from distinct perspectives in economics, strategy research and ethics. Combining insights from Austrian economics, the resource-based perspective, and finders, keepers ethics, I argue that strategy is about the discovery of hitherto unexploited possibilities for exchange. To the extent that strategy is about the discovery/creation ex nihilo of products, ways of producing products, etc., the resulting profits are argued to be justifiable from a finders, keepers perspective.